Towards a framework for modelling innovative expressions - Jane, Labadin; Soubakeavathi, Rethinasamy; Narayanan, Kulathu Ramaiyer; Lim, Phei Chin (2020)
Rubrics are powerful instruments to help direct students’ learning towards a set of pre-defined learning outcomes. Defining a set of objectively defined rubric items that also triggers critical thinking and creative expressions remains to be a big challenge. This paper explores the knowledge gaps that hinder the formulation of such rubrics. The need for an instrument to systematically identify and chart innovation is then highlighted. A framework based on Genrich Altshuler’s Theory of Inventive Problem Solving (TRIZ) is explored for formulating rubrics that correspond to and measures the learners’ stage in problem solving while explicitly linking to innovative expressions. The resulting rubrics, which separate critical thinking and problem-solving forms part of its criteria and descriptors in addressing the knowledge gaps mentioned earlier. The proposed framework has enabled the benchmarking of student works with the global collection of millions of patents and offers a new perspective for measuring the ability to innovate. Keywords: TRIZ course; critical thinking; innovative problem solving; assessment rubrics